2017
DOI: 10.1212/wnl.0000000000003951
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between carotid arterial properties and cerebral white matter hyperintensities

Abstract: Objective: Since arterial stiffness is a functional measure of arterial compliance and may be an important marker of cerebrovascular disease, we examined the association of carotid artery stiffness with white matter hyperintensity volume (WMHV) in a cross-sectional study of 1,166 strokefree participants.Methods: Carotid beta stiffness index (STIFF) was assessed by M-mode ultrasound of the common carotid artery and calculated as the ratio of natural log of the difference between systolic and diastolic blood pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 37 publications
1
39
0
Order By: Relevance
“…A previous study reported that a higher burden of WMH was found in patients with a higher degree of carotid stenosis [ 8 ]. On the other hands, arterial stiffness may explain the association between LAA and severe WMH [ 9 ]. Previous study showed that increased arterial stiffness is strongly associated with large artery atherosclerosis at various arterial trees [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study reported that a higher burden of WMH was found in patients with a higher degree of carotid stenosis [ 8 ]. On the other hands, arterial stiffness may explain the association between LAA and severe WMH [ 9 ]. Previous study showed that increased arterial stiffness is strongly associated with large artery atherosclerosis at various arterial trees [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The small vessel disease is associated with microvascular pathogenesis including endothelial dysfunction and leakage of the blood-brain barrier. Recent studies also showed that WMH is also associated with large artery atherosclerosis (LAA) [ 6 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…2. That Rundek et al 4 found this association in individuals largely without cerebrovascular disease suggests this marker may be used to detect disease while still in a preclinical state. 3.…”
Section: Discussionmentioning
confidence: 90%
“…Rundek et al 4 demonstrated that carotid artery diastolic diameter is associated with WMH in a large sample of ethnically diverse, elderly, but otherwise healthy individuals. The particular novelty is the association being preserved after covariation with known cerebrovascular disease risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation